2016
DOI: 10.1002/chem.201604415
|View full text |Cite
|
Sign up to set email alerts
|

A Masked Phosphinidene Trapped in a Fluxional NCN Pincer

Abstract: The trapping of a phosphinidene (R-P) in an NCN pincer is presented. Stabilized phosphinidene 1 was characterized by P{ H}, H, and C{ H} NMR spectroscopy, exhibiting an averaged C symmetry in solution between -60 and 60 °C. In the solid state, the phosphinidene is coordinated by one adjacent N atom featuring a formal P-N bond (1.757(2) Å) to give a five-membered ring with some aromatic character, confirmed by DFT calculations (B3LYP-D3/6-311G**++) to be the ground-state structure. Equilibration of the two N li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 53 publications
5
27
0
Order By: Relevance
“…The imine C=N distances are significantly longer [C1–N1 1.318(3) Å, C11–N3 1.309(3) Å] compared to the structure of a related proligand Ar DIP t Bu [Ar = 2,6‐dimethylphenyl; average d (C=N) = 1.27 Å], consistent with iminium and pyridinium charge delocalization character upon coordination to phosphorus. Hemilability of donor arms in phosphorus coordination complexes has been exploited to access masked Lewis acidic character for P (III) dications, and diimine‐ligated phosphinidenes . The P (I) centre has pseudo ‐T‐shaped geometry, with a tied‐back N1–P1–N3 angle of 162.75(8)° (DFT: 162.4°) and two lone pairs.…”
Section: Resultsmentioning
confidence: 99%
“…The imine C=N distances are significantly longer [C1–N1 1.318(3) Å, C11–N3 1.309(3) Å] compared to the structure of a related proligand Ar DIP t Bu [Ar = 2,6‐dimethylphenyl; average d (C=N) = 1.27 Å], consistent with iminium and pyridinium charge delocalization character upon coordination to phosphorus. Hemilability of donor arms in phosphorus coordination complexes has been exploited to access masked Lewis acidic character for P (III) dications, and diimine‐ligated phosphinidenes . The P (I) centre has pseudo ‐T‐shaped geometry, with a tied‐back N1–P1–N3 angle of 162.75(8)° (DFT: 162.4°) and two lone pairs.…”
Section: Resultsmentioning
confidence: 99%
“…Quite unexpectedly, the 1‐arsanaphthalenes (Figure D) were obtained as final products, thereby providing the first straightforward method for their synthesis. As our group and others have recently showed that 2,1‐benzazaphospholes are structurally related to 1 and also that the heavier analogues are synthetically accessible, this procedure has great potential due to its possible application within the whole of Group 15.…”
Section: Figurementioning
confidence: 99%
“…These isomers are only 0.7 (for 2 a ) and 0.2 kcal mol −1 (for 3 a ) higher in energy than their respective C 2 v symmetric ground states. However, the bond length differences between the two intramolecular N→E bonds are much less pronounced (0.2 and 0.1 Å for 2 a and 3 a , respectively) than the experimental values found for the related phosphinidenes (0.9 Å) and arsenidenes (0.5–0.7 Å) …”
Section: Resultsmentioning
confidence: 54%
“…Recently, ourselves and others have isolated N , C , N ‐chelated analogues of I , inducing the organopnictogen(I) compounds ArE ( 1 – 3 ) (Ar=2,6‐(RN=CH) 2 C 6 H 3 , E/R=As/Dmp ( 1 ), Sb/ t Bu ( 2 ), and Bi/ t Bu ( 3 ), where Dmp=2,6‐Me 2 C 6 H 3 ), and their structures have been characterized in detail by a combination of experimental and DFT studies …”
Section: Introductionmentioning
confidence: 99%